In the idiopathic inflammatory myopathies (IIM), do reactive oxygen species (ROS) contribute to muscle weakness?. Issue 7 (28th April 2015) - Lightfoot, Adam P; McArdle, Anne; Jackson, Malcolm J; Cooper, Robert G
Abstract : The idiopathic inflammatory myopathies (IIMs) are a group of rare autoimmune disorders, collectively known as myositis. Affected patients present with proximal muscle weakness, which usually improves following treatment with immunosuppressants, but often incompletely so, thus many patients remain weak. IIMs are characterised histologically by inflammatory cell infiltrates into skeletal muscle and overexpression of major histocompatibility complex I on muscle cell surfaces. Although inflammatory cell infiltrates represent a major feature of myositis there is growing evidence that muscle weakness correlates only poorly with the degree of cellular infiltration, while weakness may in fact precede such infiltrations. The mechanisms underpinning such non-immune cell mediated weakness in IIM are poorly understood. Activation of the endoplasmic reticulum stress pathways appears to be a potential contributor. Data from non-muscle cells indicate that endoplasmic reticulum stress results in altered redox homeostasis capable of causing oxidative damage. In myopathological situations other than IIM, as seen in ageing and sepsis, evidence supports an important role for reactive oxygen species (ROS). Modified ROS generation is associated with mitochondrial dysfunction, depressed force generation and activation of muscle catabolic and autophagy pathways. Despite the growing evidence demonstrating a key role for ROS in skeletal muscle dysfunction in myopathologies other than IIM, no research has yet investigated the role of modified generation of ROS in inducing the weakness characteristic of IIM. This article reviews current knowledge regarding muscle weakness in the absence of immune cells in IIM, and provides a background to the potential role of modified ROS generation as a mechanism of muscle dysfunction. The authors suggest that ROS-mediated mechanisms are potentially involved in non-immune cell mediated weakness seen in IIM and outline how these mechanisms might be investigated in this context. This appears a timely strategy, given recent developments in targeted therapies which specifically modify ROS generation.